Efektivitas Metode Role Playing dan Role Model dalam Program Kampanye Sosial (Analisis Perbedaan Efektivitas Metode Role Playing dan Role Model dalam Program Kampanye Sosial â€Produk Pangan Olahan Saguâ€ Kondur Petroleum S.A dalam Membentuk Keputusan Mengol - Galuh Gilang Pamekar (Jurnal ILMU KOMUNIKASI, 2010)
Abstract : The objective of this research is to analyze the differences on the effectiveness of role playing and role model methods applied in social campaign program. Role playing and role model are the methods in social learning theoryâ€“as a part of persuasion theoriesâ€“which implicates to behavior change by affecting with modeling and participate of the target adopters. The social campaign â€œProduk Pangan Olahan Saguâ€ adopts these two methods to persuade target adopters to change their behavior as its campaign goal.